Pemanfaatan Aplikasi Digilib UNP untuk Kebutuhan Informasi Mahasiswa Universitas Negeri Padang - Zhafiri, Shabrina; Marlini, Marlini (YASIN, 2025)
The utilization of information technology is crucial in supporting the academic information needs of university students. This study aims to describe the level of utilization of the Digilib UNP application by students at Universitas Negeri Padang and to examine the relationship between the application’s usage and the fulfillment of students’ information needs. A quantitative descriptive method was employed with a purposive sample of 93 respondents from a total population of 1,391 Digilib UNP users. Data were collected through observation and questionnaires, then analyzed using descriptive statistics and Pearson correlation tests with SPSS. The results indicate that the utilization of the Digilib UNP application falls into the good category with an average score of 2.81, while information needs, including cognitive, affective, and personal integration aspects received an average score of 2.43. Correlation analysis revealed a significant and strong relationship between the utilization of Digilib UNP and students’ information needs (r = 0.769). In conclusion, increased utilization of the Digilib UNP application correlates positively with the fulfillment of students’ academic information needs. The study’s implications emphasize the importance of optimizing application features, expanding digital collections, and strengthening students’ digital literacy as strategies to enhance the effectiveness of information technology in higher education.